(untitled) (Bangladesh Journal of Zoology, 2019)
The common passerine bird species of Bangladesh, the Black Drongo (Dicrurus macrocercus), was collected between November 2013 and March 2014 from paddy fields around the Chittagong University campus to study endohelminth parasites. In total, four helminth adult parasite species, one trematoda (Eumegacetes triangularis), one cestoda (Notopentorchis sp.), two nematoda (Viguiera dicrurusi and Diplotriaena bargusinica) and single unidentified pleurocercoid larva were evident from the body cavity and digestive tracts of the sampled birds. With prevalence, mean intensity and abundance of 52.94%, 3.33 ± 3.04 and 1.76, respectively. It was apparent that the nematodes were the most prevalent (41.18%) species and the male (60%) hosts were found to be more susceptible to infection with the helminths. The mean intensity and the abundance of male also followed the same trend. However, the maximum (100%) prevalence was in February 2014. Parasitic abundance was found to be dependent with total length (t = 40.19, p = 0.000), body length (t = 31.97, p = 0.000) and body weight (t = 39.88, p = 0.000) of the host. Among the identified helminths E. triangularis, Notopentorchis sp. and Diplotriaena bargusinica are the new records for Bangladesh and from the present host. Stomach contents showed that the bird is affirmed as insectivorous, predominant abundance of insect (97-100%) having an abundance gradient of lepidopteran > odonates > dipteran > coleopterans > hemipterans > hymenopterans. The present study coincided with the winter and spring season of an isolated study area, i.e. Chittagong University campus only. Therefore, a detailed study is expected to have a complete helminth profile and epidemiological aspects of the present host at different ecological areas of the country. Bangladesh J. Zool. 47(1): 159-171, 2019